2022
DOI: 10.1101/2022.12.14.520491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combination drug screen targeting glioblastoma core vulnerabilities reveals pharmacological synergisms

Abstract: Synergistic drug combinations are an attractive anticancer strategy but prove challenging to identify. Here we present a stepwise approach consisting in revealing core cancer vulnerabilities and exploiting them through drug combination screen to uncover synergistic treatments for glioblastoma patients. Methods: We established an innovative method, based on high-throughput screening, target deconvolution and functional genomics, to reveal core vulnerabilities in glioblastoma. Combination drug screen targeting t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Further, while Alisertib has been shown by multiple groups to reach the brain and slow brain tumor growth in vivo as described above, a recent study examining Alisertib penetrance into CNS suggests its distribution and concentrations are limited (39). Supporting this observation, Alisertib treatment alone did not slow intracranial tumor growth of transplanted GL261glioma cells, but did synergize with co-treatment of Birabresib (a BET bromodomain inhibitor) to significantly extend survival(40). Thus it is feasible that low doses of Alisertib in the brain could combine or potentiate other drug or brain targeted therapies such as TTFields.…”
Section: Discussionmentioning
confidence: 89%
“…Further, while Alisertib has been shown by multiple groups to reach the brain and slow brain tumor growth in vivo as described above, a recent study examining Alisertib penetrance into CNS suggests its distribution and concentrations are limited (39). Supporting this observation, Alisertib treatment alone did not slow intracranial tumor growth of transplanted GL261glioma cells, but did synergize with co-treatment of Birabresib (a BET bromodomain inhibitor) to significantly extend survival(40). Thus it is feasible that low doses of Alisertib in the brain could combine or potentiate other drug or brain targeted therapies such as TTFields.…”
Section: Discussionmentioning
confidence: 89%
“…An alternative method to identify drug combinations is unbiased (or hypothesis-free) screening [17]. By utilizing chemical libraries alongside the drug of interest, this has the advantage of allowing for serendipitous discoveries and can facilitate greater understanding of the polypharmacology of drugs, where subsequent target deconvolution studies of a newly identified combination can reveal novel, sometimes unexpected, mechanisms of action [18]. Moreover, when an FDA-approved library is employed, clinical translation may be accelerated.…”
Section: Introductionmentioning
confidence: 99%